Preparation of sustainable non-combustion filler substrate from waterworks sludge/aluminum slag/gypsum/silica/maifan stone for phosphorus immobilization in constructed wetlands - Wang, Guanghui (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
In this study, an artificial wetland filler matrix capable of effectively fixing phosphorus was prepared using a non-combustion process to save energy. To evaluate the adsorption performance of this filler, adsorption experiments were performed and the phosphorus adsorption mechanism characterization was studied. An alkaline environment was found to be conducive to the increase of adsorption capacity, but excessive alkalinity was not conducive to adsorption. Static adsorption experiments showed that the phosphorus removal rate could reach 95% in the simulated phosphorus-containing wastewater after adsorption completion. The adsorption process is closely simulated by the pseudo-second-kinetic adsorption model. The isothermal adsorption experiment data were consistent with the Langmuir and the Freundlich adsorption isotherms. The characterization results showed a large number of micropores and adsorption binding sites inside and on the surface of the filler. Speciation analysis on the adsorbed phosphorus revealed that chemisorption by calcium in this filler was the dominant adsorption mechanism. The research results of this study provide the basis and reference for the development of high-efficiency phosphorus removal filler in constructed wetlands